HOW DOES THE AUDIT COMMITTEE DETECT FRAUD? - Eko Sudarmanto; Imam Hidayat; Hakim, Mohamad Zulman; Adela Rhiana Novitasari; Anggun Munifatul Afifah; Pika Yolanda (ZILLZELL MEDIA PRIMA, 2024)
Financial statement fraud is a mismatch between the application of accounting principles and the preparation of financial reports with the aim of deceiving users of financial statements. This research aims to analyze the influence of the Fraud Hexagon on financial statement fraud. There are 10 variables used, namely Financial Target, Financial Stability, External Pressure, ineffective monitoring, nature of industry, collusion, change in director, change in auditor, frequent number of CEO's picture, and political connections. Financial statement fraud is measured using the Beneish M-Score Model. The sample in this research is infrastructure sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022 with the number of samples used being 29 companies. Data analysis in this study used panel data regression analysis and MRA. The results of this research show that financial stability, collusion, frequent number of ceo' pictures have a negative influence on financial statement fraud. Nature of industry and change in director have a positive influence on financial statement fraud. Meanwhile, financial targets, external pressure, ineffective monitoring, change in auditors, and political connections have no influence on the potential for fraudulent financial statements. In terms of moderating the audit committee, this variable shows that financial stability, collusion, change in directors and frequent number of CEO's pictures are capable of moderate. Meanwhile, financial targets, external pressure, ineffective monitoring, nature of industry, change in auditors and political connections are not able to moderate financial report fraud.